ANALISIS RISIKO DALAM SUPPLY CHAIN PROYEK KONSTRUKSI MENGGUNAKAN METODE HOUSE OF RISK - Ambarsari, Aulia Dewi; Nuciferani, Felicia Tria; Choiriyah, Siti; Harianto, Feri; Permatasri, Devi Indah; Wardani, Mila Kusuma (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
During the construction process of the Sidoarjo Funeral Home, issues related to material flow led to project delays and deviation from the planned schedule. Therefore, risk analysis and evaluation are crucial to address potential disruptions in the material flow. This study applies the House of Risk (HOR) method to identify, prioritize, and develop mitigation strategies for risks arising within the material flow process. The risk identification phase adopts the Supply Chain Operation Reference (SCOR) approach to determine risk events and their causes. Subsequently, calculations are conducted to prioritize risk agents and design appropriate mitigation strategies. The strategy formulation process begins by assessing the correlation between mitigation actions and risk agents, followed by the calculation of Total Effectiveness (TEk), Degree of Difficulty (Dk), and the Effectiveness to Difficulty Ratio (ETDk) to determine the ranking of mitigation priorities. The results of the study identify 19 risk events and 20 associated risk causes within the material flow. Eight mitigation strategies are proposed to address nine dominant risk causes, including: the development of Standard Operating Procedures (SOPs) as a communication system, adding security protection for materials, conducting punishment to related parties, creating an integrated system, coordinating and communicating with suppliers, making agreements with external parties, conducting training, and tightly selecting workers.